Myths and methodologies: The use of equivalence and non-inferiority tests for interventional studies in exercise physiology and sport science - Mazzolari, R.; Porcelli, S.; Bishop, D. J.; Lakens, D. (Experimental Physiology, 2022)
Exercise physiology and sport science have traditionally made use of the null hypothesis of no difference to make decisions about experimental interventions. In this article, we aim to review current statistical approaches typically used by exercise physiologists and sport scientists for the design and analysis of experimental interventions and to highlight the importance of including equivalence and non-inferiority studies, which address different research questions from deciding whether an effect is present. Initially, we briefly describe the most common approaches, along with their rationale, to investigate the effects of different interventions. We then discuss the main steps involved in the design and analysis of equivalence and non-inferiority studies, commonly performed in other research fields, with worked examples from exercise physiology and sport science scenarios. Finally, we provide recommendations to exercise physiologists and sport scientists who would like to apply the different approaches in future research. We hope this work will promote the correct use of equivalence and non-inferiority designs in exercise physiology and sport science whenever the research context, conditions, applications, researchers` interests or reasonable beliefs justify these approaches.